La política forestal de la C.E.E. - De La Riva Fernández, Juan (Geographicalia, 2017)
This work analyses the actuations that in forestry policy EEC has been carrying out since its creation. After taking into consideration the EEC forest and the characteristics of stadistic information which lies in this subject. An historic trip is made following the adoptted legislation, as well as on the consecutive attempts of the Commission in proposing to the Concil the adoption of a common forestry policy. We conclude with the analysis of the May, 1989, adoptted under the Spanish Presidency dispositions about the Forestal Action Programme.